2017
DOI: 10.1016/j.marpolbul.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics of Ulva lactuca Linnaeus (Chlorophyta) exposed to oil fuels: Fourier transform infrared spectroscopy and multivariate analysis as tools for metabolic fingerprint

Abstract: Fossil fuels, e.g. gasoline and diesel oil, account for substantial share of the pollution that affects marine ecosystems. Environmental metabolomics is an emerging field that may help unravel the effect of these xenobiotics on seaweeds and provide methodologies for biomonitoring coastal ecosystems. In the present study, FTIR and multivariate analysis were used to discriminate metabolic profiles of Ulva lactuca after in vitro exposure to diesel oil and gasoline, in combinations of concentrations (0.001%, 0.01%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…We use FTIR and multivariate analysis to discriminate metabolic profiles of Ulva lactuca after in vitro exposure to diesel oil and gasoline. As a result, Pilatti et al (2017) observed that both PCA and HCA performed on entire mid-infrared spectral window were able to discriminate diesel oil-exposed thalli from the gasoline-exposed ones. In addition to this, HCA performed in the spectral window related to protein absorbance (1700-1500 cm -1 ) allowed the best discrimination between samples exposed to gasoline and diesel oil.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We use FTIR and multivariate analysis to discriminate metabolic profiles of Ulva lactuca after in vitro exposure to diesel oil and gasoline. As a result, Pilatti et al (2017) observed that both PCA and HCA performed on entire mid-infrared spectral window were able to discriminate diesel oil-exposed thalli from the gasoline-exposed ones. In addition to this, HCA performed in the spectral window related to protein absorbance (1700-1500 cm -1 ) allowed the best discrimination between samples exposed to gasoline and diesel oil.…”
Section: Discussionmentioning
confidence: 95%
“…Combination of FTIR and multivariate analysis presents an important tool in metabolic profiles discrimination from Ulva lactuca exposed to diesel oil and gasoline. Pilatti et al (2017) observed that spectral window related to protein absorbance (1700-1500 cm−1) enabled the best discrimination between gasoline-exposed samples regarding exposure time, and between diesel oil-exposed samples.…”
Section: Introductionmentioning
confidence: 93%
“…The presence of phenol in wastewater might influence the chemical composition of activated sludge. Other studies concerning investigation of marine plant exposed to petrol and diesel changes in metabolic profile revealed that there were visible changes in FT-IR spectra of plants exposed and non-exposed to xenobiotics (Pilatti et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Performing FT-IR analysis of samples provides useful indicators to characterize changes in organic matters, without the need of extraction procedures (Bernier et al 2013 ). This analytical approach is simple, cheap and efficient in applications aimed to determine changes in investigated media (Pilatti et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation